Proposta de modificação de metodologia de previsão de deslocamentos horizontais de estacas hélice contínua em solo Granular - Oliveira, Felipe Freitas de (2020)
This research presents a study on continuous propeller piles with the objective of propose modifications in the methods available in the literature for the prediction of horizontal displacements in soil profiles predominantly granular in shape to provide more consistent results with those obtained experimentally. For this, data were obtained from ten horizontal load tests (SHPs) on 600 mm in diameter and variable length, held in the city of Paulino Neves, in Maranhão. Initially, load x displacement curves were predicted from changes in the parameters used in the method of Matlock and Reese (1961) and were empirical proposals are presented for the calculation of the horizontal reaction coefficient (nh) of granular soils aiming at better convergences in the prediction of the horizontal behavior of piles. Subsequently, load x displacement curves (Hy) were predicted at the top of the pile. using the RS Pile software and, along the depth, p-y and y-z curves using the RS Pile and PyPile software, in both cases using the API (2000) and Reese et al. (1975). The forecast results were then compared to the results obtained from the SHPs. Predictions made from changes in parameters used in the method of Matlock and Reese (1961) were convergent with the values experimental for all the proposals made. Forecasts made with the use of software at the top of the piles showed that the API method (2000) predicted more H-y curves concordant in relation to the SHP's experimental displacements. Along the depth, the p-y curves predicted by the methods used were coincident for low loads and diverged to higher loads, and the y-z curves were coincident for the pile SHP 10 and with small divergences at the top for SHPs 2, 5 and 6.